New anti-diabetic drug Morus alba L. (Sangzhi) alkaloids (SZ-A) improves diabetic nephropathy through ameliorating inflammation and fibrosis in diabetic rats - Li, Caina; Liu, Quan; Ji, Wenming; Fu, Yaxin; Cao, Hui; Huan, Yi; Lei, Lei; Gao, Xuefeng; Chen, Leilei; Feng, Cunyu; Zhang, Lin; Li, Pingping; et al. (Frontiers in Medicine, 2023)
Background Morus alba L. (Sangzhi) alkaloid (SZ-A) is a new antidiabetic drug approved by the China National Medical Products Administration in 2020. Diabetic nephropathy (DN) is a common diabetic complication and an important cause of morbidity and mortality in patients with diabetes. The effects of SZ-A on DN remain unknown. Purpose This study evaluated the effects of SZ-A on DN in Zucker diabetic fatty (ZDF) rats and explored the underlying mechanisms based on nitrosative stress, inflammation, and fibrosis. Methods Diabetic ZDF rats were orally administered 100 and 200 mg/kg of SZ-A once daily for 9 weeks. The glucose metabolism and kidney function were assayed. The pathological injury and fibrosis of the kidneys were separately evaluated using hematoxylin and eosin staining and Masson’s staining. The oxidative and nitrosative stress and inflammation were assayed by determining the levels of related indices in the blood and kidneys and quantifying the related gene and protein expression. The expression of transforming growth factor β1 (TGFβ1) gene and protein were assayed by quantitative real-time PCR and immunohistochemistry, respectively. The renal transcriptomics was analyzed using RNA sequencing. Results Repeated treatment with SZ-A significantly improved glucose metabolism, dose-dependently decreased the levels of blood urea nitrogen, urinary albumin, and β2-microglobulin, and evidently relieved the renal injury in diabetic ZDF rats. As for the mechanisms, SZ-A remarkably ameliorated systemic nitrosative stress through lowering the levels of blood inducible nitric oxide synthase and nitric oxide, and significantly relieved systemic and renal inflammation by reducing the levels of blood interleukin-1β and monocyte chemoattractant protein-1 (MCP-1) and decreasing the levels of renal C-reactive protein content and expression of tumor necrosis factor-α in the kidneys. SZ-A also improved renal fibrosis by lowering the expression of TGFβ1 in the kidneys. Additionally, SZ-A significantly lowered the expression of stimulator of chondrogenesis 1 in the kidneys. Conclusion Repeated treatments with SZ-A significantly ameliorates DN by regulating systemic nitrosative stress, renal inflammation, and renal fibrosis partially through inhibition of the cytokine-NO and TGF-β1 signaling in ZDF rats, providing evidence for the additional application of SZ-A in clinical use for the treatment of DN.